LEGALITY OF ELECTRONIC AGREEMENTS BASED ON THE CIVIL CODE AND THE LAW ON ELECTRONIC INFORMATION AND TRANSACTIONS - Ade Pratiwi Susanty, (Proceeding International Conference on Social Sciences, 2026)
Based on Article 1313 of the Civil Code, it is explained that an agreement is an act in which one or more people bind themselves to one or more other people. Technological developments have indirectly resulted in the birth of new forms of legal acts that were previously not regulated in laws and regulations, for example electronic agreements. This study aims to explain the legality of electronic agreements based on the Civil Code and the Electronic Information and Transactions Law. The method used in this study is normative legal research using a statutory regulatory approach. Based on Article 1320 of the Civil Code, it is stated that the conditions for a valid agreement are the agreement of the parties, the capacity of the parties, the existence of a certain subject matter, and certain subjects that are lawful. The agreement of the parties in the agreement is evidenced by the signatures of the parties. An electronic agreement is an agreement between the parties made through a series of electronic devices and procedures that function to prepare, collect, process, analyze, store, display, announce, send, and/or disseminate electronic information using electronic signatures. Based on the Electronic Information and Transactions Law, a valid electronic agreement is an electronic agreement that uses a certified electronic signature